Non-traditional security issues in ASEAN : agendas for action - Anthony, Mely Caballero; Gong, Lina (ISEAS Publishing, 2020)
Non-Traditional Security Issues in ASEAN examines the current state of governance of non-traditional security challenges confronting the ASEAN region. The book takes an issue-specific approach to investigating how ASEAN states and societies govern many of the pressing non-traditional security issues, such as climate change, food security, environmental protection, humanitarian assistance and disaster response, health security, nuclear security, and human trafficking and forced displacement.